Penerapan Arsitektur Perilaku dalam Perancangan Sekolah Tahfidzul Qur’an di Kabupaten Takalar - A Yunikha Citra; Amin, Burhanuddin; Alfiah, Alfiah (TIMPALAJA : Architecture Student Journals, 2024)
This study investigates the application of Islamic architectural principles in the design of an Islamic Center in Bulukumba Regency, Indonesia. As a region focused on religious activities, Bulukumba requires a venue for both the community and government to conduct these activities, in the form of an Islamic Cultural Center. The center is intended to accommodate various social, educational, health, economic, and Islamic propagation activities, while serving as a cultural landmark reflecting the spiritual and communal identity of the Muslim community. The study highlights the importance of integrating geometric patterns and traditional materials to create spaces that promote Islamic cultural values and historical symbolism, alongside designing supportive facilities. The proposed framework considers fundamental Islamic principles derived from the Qur'an and Hadith, adapted to the local context of Bulukumba. The primary objective of this study is to enhance understanding of how architectural elements can enrich the functionality and cultural significance of the Islamic Center, contributing significantly to the development of contemporary architecture in Indonesia